Analysis Of Factors Causing Low Level Of Community Education In Batu Tiga Village, Boleng District, West Manggarai Regency - Sarwan, Sarwan; Muhammad Yusuf; Aulia, Aulia (International Journal of Economic Research and Financial Accounting, 2024)
This research uses a qualitative approach with descriptive research or what is usually called qualitative descriptive research. The informants used were main, key and supporting or additional informants who were determined based on purposive sampling techniques. The type of data used in this research is qualitative data obtained based on data collection techniques through observation, short interviews, documentation and giving questionnaires related to the problem being studied. The data analysis technique used is the Miles and Huberman method, namely data reduction, data presentation and drawing conclusions. The results of the research show that the factors causing the low level of community education in Batu Tiga Village, Boleng District, West Manggarai Regency are internal factors (lack of individual motivation, lack of individual awareness, lack of interest in learning & school, no desire to continue education, and wanting to find work/help people parents) and external factors (economic conditions, lack of parental motivation, social conditions/community environment/peers, accessibility/distance from home to school or college, lack of parental attention, cultural factors, parental education level and educational infrastructure not feasible and there is a new factor that emerges, namely the parent's death factor).